IMPLIKATUR 'MEME' DENGAN KATA 'TENGGELAMKAN' - Sela Wildaan Aulia (Faculty of Cultures and Languages UIN Raden Mas Said, 2021)
The majority of Indonesians who are known to use social media as a means of communication and entertainment are certainly no strangers to the term ‘meme’. A popular meme phenomenon is the use of the word tenggelamkan (sink) at the end of the discourse popularized by Susi Pujiastuti, the former Minister of Fisheries and Marine Affairs. The purposes of this study was to find out the styles of language used in memes using the word tenggelamkan and their implications. The data of this study were taken from various pictures on the Internet with 15 memes in total. The method applied was descriptive-qualitative by using Grice’s theory of conversation maxims. The results of this study show that the themes used in memes with the word tenggelamkan include love, friendship, corruption, worship, and food. The use of language styles reflected from the memes are cynicism, paradoxes, and rhetoric. Meanwhile, the impicatures of meme the memes comprise satire, suggestion, and a combination of both.